Pengaruh Kualitas Layanan, Kualitas Produk, Dan Harga Terhadap Keputusan Pembelian (Studi Kasus Pada Pelanggan Ayam Nelongso Cabang Tlogomas) - Yuliadi, Rahmad Agung; Widarko, Agus; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The aim of this research is to determine and analyze the simultaneous and partial influence of service quality, product quality and price on purchasing decisions for consumers of Nelongso Fried Chicken, Tlogomas Branch. The total population in the study reached a total of 600 consumers with a sample of 86 respondents using the Slovin formula. This type of research is quantitative research with a purposive sampling technique approach. This research source uses primary data sources and the data collection method uses a questionnaire. This research was tested using instrument tests, normality tests, classical assumption tests, multiple linear regression, and hypothesis tests. Based on the results of the research and discussion, it can be seen that service quality, product quality and price have a simultaneous and partial effect on purchasing decisions for consumers of Nelongso Fried Chicken, Tlogomas Branch. Keywords: Service Quality, Product Quality, Price, Buying Decision